2019
DOI: 10.1002/jbm.a.36797
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PRP and LyPRP on osteogenic differentiation of MSCs

Abstract: Platelet-rich plasma (PRP) is rich in a variety of growth factors and plays an important role in the proliferation and differentiation of mesenchymal stem cells (MSCs). It has been reported that the preparation of freeze-dried platelets (lyophilized platelets [LyPRP]) from platelets could be an effective strategy to preserve the bioactivity of platelets for a long time. In this study, the osteogenic induction effects of PRP and LyPRP on MSCs were evaluated. The rabbit arterial blood was drawing to preparation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…However, IPFP-MSCs had less expression of chondrogenic markers in PRP group. We presumed that PRP could promote the osteogenic differentiation of MSCs as some studies have shown [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, IPFP-MSCs had less expression of chondrogenic markers in PRP group. We presumed that PRP could promote the osteogenic differentiation of MSCs as some studies have shown [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the equivalence between fresh-frozen PRP and FD-PRP was shown in terms of PDGF-BB, TGF-Ī² and VEGF concentrations and stimulation of bone formation in immunocompromised mice [64]. However, in an apparent contradiction, rabbit BMSCs differentiation and proliferation was better in CaCl 2 -activated fresh PRP compared with FD-PRP [65].…”
Section: Dentistry Researchmentioning
confidence: 98%
“…Electrospinning nanofibers with sustained release of growth factors have the great potential to create a beneficial microenvironment for bone tissue formation, including promoting migration and differentiation of osteoblasts by angiogenic, inflammatory, and bone formation enhancement (Sui et al, 2007;Vo et al, 2012). It is interesting that the cytokines from PRF also have similar biological functions for tissue regenerative medicine, such as anti-inflammation effects, promoting osteogenic differentiation and vascularization (Pietramaggiori et al, 2006;You et al, 2019;Nasirzade et al, 2020;Xie et al, 2020;Zhang et al, 2020). In present study, we investigated the effect of extract of PVA/SA/PRF nanofibers on proliferation and osteogenesis of osteogenic precursor cells (MEC3T3-E1 cells) in vitro.…”
Section: Discussionmentioning
confidence: 99%